2014
DOI: 10.1155/2014/203930
|View full text |Cite|
|
Sign up to set email alerts
|

Meta-Analysis: Overweight, Obesity, and Parkinson's Disease

Abstract: Objective. Parkinson's disease (PD) is a severe neurological disease and its risk factors remain largely unknown. A meta-analysis was carried out to investigate the relationship of overweight and obesity with PD. Methods. We used PubMed, EMBASE, and the Chinese National Knowledge Infrastructure (CNKI) databases to identify studies of associations between overweight/obesity and PD. Overweight, obesity, and PD were used as keywords, and published works were retrieved until September 30, 2013. The extracted data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 26 publications
0
41
0
1
Order By: Relevance
“…Most cases of OSA in this study, therefore, were diagnosed on the basis of clinical symptoms (witnessed persistent snoring and apnea). As the positive predictive rate of snoring in detecting OSA was approximately 66.2% (Chen et al ., ), we surmised that the positive predictive rate of witnessed snoring plus apnea should be higher than that of snoring only, although the exact value has never been reported.…”
Section: Methodsmentioning
confidence: 86%
“…Most cases of OSA in this study, therefore, were diagnosed on the basis of clinical symptoms (witnessed persistent snoring and apnea). As the positive predictive rate of snoring in detecting OSA was approximately 66.2% (Chen et al ., ), we surmised that the positive predictive rate of witnessed snoring plus apnea should be higher than that of snoring only, although the exact value has never been reported.…”
Section: Methodsmentioning
confidence: 86%
“…Physical inactivity is associated with the development of many devastating chronic diseases, including type 2 diabetes and obesity . Some studies suggest a relationship between insulin resistance, diabetes, obesity, dyslipidemia, or diet and the development of PD (Table ) . Together, these traits define an endocrine disease of epidemic proportion rooted in systemic inflammation and oxidative stress: metabolic syndrome (MetS) .…”
Section: Physical Inactivity: Parkinson's Disease and Metabolic Syndromementioning
confidence: 99%
“…24 Some studies suggest a relationship between insulin resistance, diabetes, obesity, dyslipidemia, or diet and the development of PD (Table 2). 27,[62][63][64][65][66][67][68][69][70][71] Together, these traits define an endocrine disease of epidemic proportion rooted in systemic inflammation and oxidative stress: metabolic syndrome (MetS). 26 MetS is a cluster of abnormalities that contribute to an increased risk of cardiovascular disease, type 2 diabetes mellitus, kidney disease, and overall mortality.…”
Section: Physical Inactivity: Parkinson's Disease and Metabolic Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol consumption, calcium channel blocker use, coffee consumption and non-steroidal anti-inflammatory drug use have been associated with relative risk reductions [1], and interestingly and most controversial, numerous epidemiologic studies showed that tobacco smoking could also be a protective factor for PD [6][7][8]. The role of excess body weight and its association with PD risk is still unclear [1,9,10].…”
Section: Introductionmentioning
confidence: 99%